Soy Formula as An Alternative for Infants with Cow’s Milk Allergy: Perspective from Pediatricians and Midwives in Indonesia - Chandra Khoe, Levina; Sitorus, Nova (Ridwan Institute, 2023)
The prevalence of food allergy in children is increasing globally, with cow's milk allergy beingthe most common in infants and increasing from 2% to 3% in developed countries. However, data oncow's milk allergy in infants is limited in Indonesia. This study used a mixed methods approach using anonline survey and in-depth interviews. The survey was conducted from September 2021 to March 2022.Qualitative analysis, all interviews were recorded and transcribed. Data were analyzed using simplethematic analysis. The results showed that a total of 93 pediatricians and 104 midwives participated inthe survey. However, among the 93 pediatricians, only 56 (60.2%) completed the survey. Meanwhile, 11midwives (10.6%) were excluded because they had no experience in handling CMA cases. The majorityof CMA cases occurred in children under two years old, and most were treated by pediatricians. In termsof diagnostic tests, 51.8% of pediatricians recommended all specific IgE tests, prick tests, and provocationtests to diagnose allergies. More than 80% (46/56) of pediatricians chose to avoid all types of cow's milkproducts in the mother and child's diet as the main treatment. Meanwhile, only 22.1% of midwives didthe same. Milk choice will differ depending on the severity of CMA. Soy milk formula is preferred bymidwives for patients with low-level and moderate to severe allergies. Meanwhile, pediatriciansrecommend extensive hydrolysate formula for low severity patients and amino acid-based formula formoderate to severe.